26.2k views
1 vote
Hi guys,

I've got the following problem:

I've tried to apply the chain rule but I just don't get the right answer. Can anyone help me? :)

Hi guys, I've got the following problem: I've tried to apply the chain rule but I-example-1

1 Answer

2 votes


\begin{bmatrix}u\\v\end{bmatrix}=\begin{bmatrix}\cos\theta&-\sin\theta\\\sin\theta&\cos\theta\end{bmatrix}\begin{bmatrix}x\\y\end{bmatrix}=\begin{bmatrix}x\cos\theta-y\sin\theta\\x\sin\theta+y\cos\theta\end{bmatrix}

so that


\begin{cases}u(x,y)=x\cos\theta-y\sin\theta\\v(x,y)=x\sin\theta+y\cos\theta\end{cases}

For a function
f(u,v)=f(u(x,y),v(x,y)), we have by the chain rule,


(\partial f)/(\partial x)=(\partial f)/(\partial u)(\partial u)/(\partial x)+(\partial f)/(\partial v)(\partial v)/(\partial x)

and


\begin{cases}(\partial u)/(\partial x)=\cos\theta\\\\(\partial v)/(\partial x)=\sin\theta\end{cases}


\implies(\partial f)/(\partial x)=\cos\theta(\partial f)/(\partial u)+\sin\theta(\partial f)/(\partial v)

Let
g(u,v)=(\partial f)/(\partial u) and
h(u,v)=(\partial f)/(\partial v). This substitution is made just to make the application of the chain rule clearer.


(\partial f)/(\partial x)=\cos\theta\,g+\sin\theta\,h

Differentiating again wrt
x gives


(\partial^2f)/(\partial x^2)=\cos\theta(\partial g)/(\partial x)+\sin\theta(\partial h)/(\partial x)

By the chain rule,


(\partial g)/(\partial x)=(\partial g)/(\partial u)(\partial u)/(\partial x)+(\partial g)/(\partial v)(\partial v)/(\partial x)

and our substitution shows that, for instance,


(\partial g)/(\partial u)=(\partial)/(\partial u)(\partial f)/(\partial u)=(\partial^2f)/(\partial u^2)

and so


(\partial g)/(\partial x)=\cos\theta(\partial^2f)/(\partial u^2)+\sin\theta(\partial^2f)/(\partial v\partial u)

Similarly, we find


(\partial h)/(\partial x)=\cos\theta(\partial^2f)/(\partial u\partial v)+\sin\theta(\partial^2f)/(\partial v^2)

Putting everything together, we have


(\partial^2f)/(\partial x^2)=\cos^2\theta(\partial^2f)/(\partial u^2)+\cos\theta\sin\theta(\partial^2f)/(\partial v\partial u)+\sin\theta\cos\theta(\partial^2f)/(\partial u\partial v)+\sin^2\theta(\partial^2f)/(\partial v^2)

and we can similarly find that


(\partial^2f)/(\partial y^2)=\sin^2\theta(\partial^2f)/(\partial u^2)-\cos\theta\sin\theta(\partial^2f)/(\partial v\partial u)-\sin\theta\cos\theta(\partial^2f)/(\partial u\partial v)+\cos^2\theta(\partial^2f)/(\partial v^2)

Adding together these derivatives, we see the mixed partials cancel, and recalling that
\cos^2\theta+\sin^2\theta=1, we end up with


(\partial^2f)/(\partial x^2)+(\partial^2f)/(\partial y^2)=(\partial^2f)/(\partial u^2)+(\partial^2f)/(\partial v^2)

as required.

User Yotka
by
6.1k points